1993
DOI: 10.1021/np50096a006
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Inhibitors of Skin Tumor Promotion, XII. Rotenoids from Amorpha fruticosa

Abstract: As a part of screening studies for chemopreventive agents (anti-tumor-promoters), six North American plants belonging to the Amorpha genus were tested using an in vitro assay system. Of these plants, Amorpha fruticosa exhibited strong inhibitory effects on Epstein-Barr virus early antigen (EBA-EA) activation induced by the tumor promoter 12-O-tetradecanoylphorbol-13-acetate (TPA). Also six rotenoids, amorphispironone [1], tephrosin [2], amorphigenin [3], 12a-hydroxyamorphigenin [4], 12a-hydroxydalpanol [5], an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…The pods (Brett 1946) and leaves (Cao et al 1996) contain natural insecticides. Chemicals isolated from the leaves of false indigo have demonstrated extremely high anti-tumor promoting activities (Konoshima et al 1993). Because of its spring flower display, false indigo is also used horticulturally (Simpson et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The pods (Brett 1946) and leaves (Cao et al 1996) contain natural insecticides. Chemicals isolated from the leaves of false indigo have demonstrated extremely high anti-tumor promoting activities (Konoshima et al 1993). Because of its spring flower display, false indigo is also used horticulturally (Simpson et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a series of papers on isolation of the same and some new rotenoids followed, usually applying conventional column chromatography on various stationary phases complemented with preparative or semi-preparative HPLC (Konoshima et al, 1993; Terada et al, 1993; Lee et al, 2006a,b; Kim et al, 2011; Wu et al, 2015; Muharini et al, 2017). …”
Section: Phytochemical Constituents Of Amorpha Fruticosa: Isoflavonoimentioning
confidence: 99%
“…As a part of screening studies for cytotoxic agents (anti-tumor-promoters), six North American plants belonging to the Amorpha genus were tested using an in vitro assay (Konoshima et al, 1993). Authors found that A. fruticosa exhibited strong inhibitory effects on Epstein-Barr virus early antigen (EBA-EA) activation induced by 12- O -tetradecanoylphorbol-13-acetate.…”
Section: Pharmacological Activity Of Amorpha Fruticosa: Cytotoxicitymentioning
confidence: 99%
“…20,21 TSN has been shown to inhibit mouse skin tumor promotion and invasion of cancer cells. 22,23 We have previously shown that TSN inhibited nuclear factor-kB activity and induced internalization and degradation of epidermal growth factor receptor. 24,25 As part of our continuing search for compounds to enhance the cytotoxic activity of 2-DG from natural products, we found that TSN enhanced the cytotoxic activity of 2-DG against various human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%